Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Dalam Pembelian Produk Fashion - Risman Sababalat; Dokman Marulitua Situmorang (Jurnal Minfo Polgan, 2026)
This study aims to examine the effect of product quality and service quality on consumer satisfaction in purchasing fashion products through Online and Offline channels, and to analyze the differences in consumer satisfaction levels between the two channels. The study used a quantitative approach with a survey method and purposive sampling technique. Data were collected from 100 active students of the Bukit Pengharapan Christian Institute (IKBP) who had experience purchasing fashion products through both channels. Data analysis used multiple linear regression separately for Online and Offline contexts, as well as a Paired Sample T-test to compare satisfaction levels between the two channels. The results showed that product quality had a positive and significant effect on consumer satisfaction in both Online and Offline purchases. Service quality also had a positive and significant effect on both Online and Offline purchases. Simultaneously, both variables explained 83.4% of the variation in satisfaction in Online purchases (R²=0.834) and 85.2% in Offline purchases (R²=0.852). However, a peered sample t-test showed no significant difference in satisfaction between the two channels (t=−1.470; sig=0.145). These findings imply that fashion businesses need to simultaneously improve product quality and service quality across both channels to enhance consumer satisfaction. Future research is recommended to incorporate additional variables such as price perception and brand trust across a broader and more diverse population